O21.4 Decreased cellular energy in the brain frontal white matter is associated with past immunosuppresion in chronic hiv infection. (13th September 2015) - Cysique, LA; Juge, L; Brew, BJ; Rae, C
Abstract : Background: Long-term brain neurochemical changes are not clearly understood in HIV-infected adults who are ageing and are otherwise clinically stable. Methods: Forty men (mean age = 54 ± 7), 20 HIV-infected (70% with historical AIDS, nadir CD4 ≤350, all on antiretroviral treatment and virally suppressed), and 20 demographically comparable HIV-uninfected controls were enrolled into a prospective observational cohort study. All underwent standard neuropsychological testing to determine the level of neurocognitive performance over an 18-month period, and a proton magnetic resonance spectroscopy scan of the brain frontal white matter to assess in vivo neurochemical information. Clinically relevant neuropsychological change over the study period was determined using neurocognitive norms for change. Major brain metabolites: Creatine, N-Acetyl Aspartate, Choline, Glutamate/Glutamine and Myo-Inositol were fitted in jMRUI in reference to water. Brain metabolites' change was determined using linear regression with a time effect, a group effect and a time*group interaction effect. Data were randomly selected from the larger baseline cohort (N = 120) for this preliminary analysis. Results: Over the 18 months period, neurocognitive performance change did not differ between HIV-infected and controls. Creatine significantly decreased in the HIV-infected compared to the controls (p < 0.03). Myo-Inositol and Glutamate/Glutamine increased as a function of time (p < 0.0001) but equally in both groups. When adjusting our analyses for age, we corroborated an age*group effect (p < 0.03) on reduced N-Acetyl Aspartate in the HIV-infected participants, while the decreasing Creatine results were maintained. Among the HIV disease biomarkers including viral load blips over the study period, only a lower nadir was associated with decreasing Creatine (Spearman Rho r = -.49, p < 0.03). Conclusions: Chronic HIV infection is associated with subclinical cellular energy abnormalities (Creatine) linked to past levels of immunosuppression and acceleration of neuronal integrity (N-Acetyl Aspartate). This preliminary study further reinforces the need for longer-term follow-up in chronic HIV-infected ageing persons to determine the prognostic value of these findings. Disclosures: This project was supported in part by NHMRC project grant ID568746, NHMRC Career Development Fellowship APP1045400 and Abbvie research grant supporting the acquisition of the follow-up MRI (CIA Cysique). BJB has received research funding, consultancy fees, and lecture and travel sponsorships from Gilead Sciences, ViiV Healthcare, and MSD. LAC has received research support from MSD, Abbvie, Gilead Sciences, and ViiVhealthcare. LAC has received honoraria from Abbvie and ViiVHealthcare.